Social relations and presence of others predict bystander intervention: Evidence from violent incidents captured on CCTV. Issue 6 (29th July 2019) - Liebst, Lasse Suonperä; Philpot, Richard; Bernasco, Wim; Dausel, Kasper Lykke; Ejbye‐Ernst, Peter; Nicolaisen, Mathias Holst; Lindegaard, Marie Rosenkrantz
Abstract: Are individuals willing to intervene in public violence? Half a century of research on the "bystander effect" suggests that the more bystanders present at an emergency, the less likely each of them is to provide help. However, recent meta‐analytical evidence questions whether this effect generalizes to violent emergencies. Besides the number of bystanders present, an alternative line of research suggests that pre‐existing social relations between bystanders and conflict participants are important for explaining whether bystanders provide help. The current paper offers a rare comparison of both factors—social relations and the number of bystanders present—as predictors of bystander intervention in real‐life violent emergencies. We systematically observed the behavior of 764 bystanders across 81 violent incidents recorded by surveillance cameras in Copenhagen, Denmark. Bystanders were sampled with a case–control design, their behavior was observed and coded, and the probability of intervention was estimated with multilevel regression analyses. The results confirm our predicted association between social relations and intervention. However, rather than the expected reversed bystander effect, we found a classical bystander effect, as bystanders were less likely to intervene with increasing bystander presence. The effect of social relations on intervention was larger in magnitude than the effect of the number of bystanders. We assess these findings in light of recent discussions about the influence of group size and social relations in human helping. Further, we discuss the utility of video data for the assessment of real‐life bystander behavior.